Relations between Proactive Coping with Psychological Stress and some Variables among a Sample of Employees in Aleppo, Syria - Fayez K. Alhussein (Sultan Qaboos University, 2015)
This study aimed to identify differences between the mean scores of the sample due to sex, work sector (public vs. private), and age. The study also aimed to gauge the morale of the sample regarding their jobs. The researcher used a scale to measure proactive coping with stress (Greenglass). The scale was administered to a sample of 280 workers and employees in the city of Aleppo in Syria. No statistically significant differences were found between the mean scores for males and females; young or old, public and private. However, morale was significantly related to proactive coping to stress. Employees with higher morale coped better with psychological stress than those with lower morale.